Pengaruh Desain Produk, Gaya Hidup, Kepercayaan Merek Dan Pengalaman Pengguna Terhadap Keputusan Pembelian Sepeda Motor Honda PCX Di Kota Klaten - Hendra Laksana Putra; Atik Lusia (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
This research was conducted to analyze the effect of product design, lifestyle, brand trust, and user experience on purchasing decisions of Honda PCX motorbikes. The data collection method in this study used a questionnaire filled out by respondents, namely people who had bought and used a Honda PCX motorcycle. By taking a sample of 126 respondents in this study using a purposive sampling method and using the Hair formula, et al, the sampling method used in this study was SPSS 25, and the analysis technique used in this research is validity test, reliability test, classical assumption test, and hypothesis test. The secondary data obtained comes from books that reveal purchasing decisions, the internet and previous research journals. The results of the study show that simultaneously (F test) indicates that there is a significant influence between product design, brand trust lifestyle, and user experience. Partially (t test) product design, brand trust, lifestyle and user experience have a significant effect on purchasing decisions. According to the results obtained from the output of data processing, it is known that the coefficient of determination (R Square) is 0.535 which means that product design, lifestyle, brand trust and user experience influence purchasing decisions by 53.5% while the remaining 46.5% determined by other variables not examined in this study.